THE SIGNIFICANCE OF APPLYING VARIOUS APPROACHES IN TEACHING ENGLISH - Rustamova Shahnoza Aripovna; Olimjonov Ibrohim Soyibjon o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Technology has changed the world dramatically over the last decade. Language learning technology makes it much easier to teach and learn a foreign language in a convenient way. You can access them from anywhere and even take them with you when you are on the move. Technology has not only altered the way languages are taught but also made learning more available, engaging, and adapted for students worldwide. In this article we are going to discuss how technology can support foreign language teachers and their students. important